1999
DOI: 10.1097/00000539-199911000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Intravascular Volume Replacement Regimens on Renal Function in the Elderly

Abstract: We evaluated the effects of epidural anesthesia and halothane anesthesia on the vasoconstrictive properties of a cell-free hemoglobin solution. The vasoconstriction caused by a cell-free hemoglobin solution was similar in unanesthetized sheep and sheep with thoracic epidural anesthesia and was reduced in sheep with halothane anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 12 publications
3
44
0
5
Order By: Relevance
“…Regarding NAG, a subtle marker for tubular changes, no group differences could be found. This is in line with prior data in elderly patients [19,23].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding NAG, a subtle marker for tubular changes, no group differences could be found. This is in line with prior data in elderly patients [19,23].…”
Section: Discussionsupporting
confidence: 92%
“…Some reports have shown that HES has no adverse infl uence on renal function in surgical patients [19,20], while other reports have shown that HES may impair renal function in surgical patients [21,22]. A recent review suggested that HES may have adverse effects on renal function, regardless of its molecular weight, DS, or C2/C6 ratio [23].…”
Section: Discussionmentioning
confidence: 99%
“…Insufficiently treated hypovolemia may also induce renal dysfunction and treatment by the administration of crystalloids alone may not achieve restoration of blood volume. Other researchers failed to find any deterioration in renal function associated with the use of various HES preparations: 6% HES 200/0.5 and HES 70/0.5 [101], 6% HES 200/ 0.5, 6% HES 200/0.62, and 6% HES 670/0.75 [107], even when high doses were used [108].…”
Section: Renal Functionmentioning
confidence: 96%
“…The use of HES 200/0.5 over 5 days in a study of critically ill patients in the intensive care unit was without negative effects on renal function compared to albumin [56]. In a study in elderly patients ([75 years old) undergoing major abdominal or cardiac surgery, administration of 6% HES 200/0.5 [101] or 130/0.4 [76,84,102] was not associated with changes in markers of renal dysfunction as compared with albumin or gelatin [102]. In fact, in studies of patients undergoing cardiac surgery [103] or elective aortic aneurysm surgery [104], renal profile according to sensitive kidney-specific markers or creatinine clearance in the group that received gelatin was slightly worse than in the HES 130/0.4 or 200/0.5 groups [103,104].…”
Section: Renal Functionmentioning
confidence: 99%